Recent Studies of African History in Japan - Philips, John Edward (History compass, 2009)
African history in Japan is a tiny part of the total output of history in Japan. It is difficult to categorize within the traditional divisions of history in Japan, and it is somewhat of an orphan, although it has been recognized as a subfield. Sub-Saharan Africa in precolonial times is considered the domain of anthropology, not history, despite the fact that Japanese archeology is considered history rather than anthropology. Most historical works concerning sub-Saharan Africa in Japan are concerned with colonialism and/or economic history, although such recent trends as subaltern studies and gender studies have also had an impact. The traditional history of North Africa and Northern, Semitic Ethiopia is also considered history in Japan.